Total immersion strategies - A closer look - Sanders, R. (coachesinfo.com, 2009)
Additional insight to the book Total Immersion, where Terry Laughlin and John Delves express ideas related to swimming more efficiently in an entertaining and effective manner. Chapter 2 in particular - entitled Swim Better Without Getting Any Stronger? Yes! - has great appeal. Additional insight can be gained by considering factors, from a biomechanical perspective, that might contribute to the success of the strategies applied in the Total Immersion program.